COQ6 mutation in patients with nephrotic syndrome, sensorineural deafness, and optic atrophy - R. Justine Perrin; Caroline Rousset‐Rouvière; Florentine Garaix; Aline Cano; John Conrath; Olivia Boyer; Michel Tsimaratos (JIMD Reports, 2020)
Abstract Introduction Primary coenzyme Q10 (CoQ10) deficiencies are a group of mitochondrial disorders that has proven responsiveness to replacement therapy. Mutations in enzymes involved in the biosynthesis of CoQ10 genes are associated with these deficits. The clinical presentation of this rare autosomal recessive disorder is heterogeneous and depends on the gene involved. Mutations in the COQ2, COQ6, PDSS2, and ADCK4 genes are responsible for steroid‐resistant nephrotic syndrome (SRNS), which is associated with extra‐renal symptoms. Previous studies have reported COQ6 mutations in 11 patients from five different families presenting with SRNS and sensorineural deafness. Case reports Our study reports the cases of two brothers of Turkish origin with renal failure and sensorineural deafness associated with COQ6 mutations responsible of CoQ10 deficiency. Optical symptoms were present in the eldest, that improved with Idebenone. Conclusion/Discussion For the first time, COQ6 mutation with optical involvement is associated with renal and hearing impairment. Although the response to replacement CoQ10 therapy was difficult to evaluate, we think that this treatment was able to stop the disease progression in both patients, and even to prevent the occurrence/development of optical and neurological impairment in the younger brother. Mitochondrial dysfunction secondary to CoQ10 deficiency should always be suspected in patients with SRNS and extra‐renal symptoms. Early recognition of this genetic SRNS is mandatory since SRNS can be avoided by adequate treatment based on CoQ10 supplement or an analogue. All cases of primary CoQ10 deficiency should be treated at an early stage to limit the progression of lesions and prevent the emergence of new symptoms.